2017
DOI: 10.1038/s41598-017-02304-z
|View full text |Cite
|
Sign up to set email alerts
|

Brain Structural Networks Associated with Intelligence and Visuomotor Ability

Abstract: Increasing evidence indicates that multiple structures in the brain are associated with intelligence and cognitive function at the network level. The association between the grey matter (GM) structural network and intelligence and cognition is not well understood. We applied a multivariate approach to identify the pattern of GM and link the structural network to intelligence and cognitive functions. Structural magnetic resonance imaging was acquired from 92 healthy individuals. Source-based morphometry analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 88 publications
8
28
0
1
Order By: Relevance
“…The associations with general cognitive function and general psychopathology were expected based on previous research in adults (26,31,32), and add to the growing database supporting a cerebellar role in cognition and affect (60). Of note, the voxelwise analyses ( Figure 3d) revealed an anatomically widespread pattern for general cognitive function, while general psychopathology showed a more restricted pattern, largely overlapping with that seen for the psychosis domain.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The associations with general cognitive function and general psychopathology were expected based on previous research in adults (26,31,32), and add to the growing database supporting a cerebellar role in cognition and affect (60). Of note, the voxelwise analyses ( Figure 3d) revealed an anatomically widespread pattern for general cognitive function, while general psychopathology showed a more restricted pattern, largely overlapping with that seen for the psychosis domain.…”
Section: Discussionsupporting
confidence: 80%
“…Further, to confirm convergence across methodological approaches, we also tested for structure-function associations at the resolution levels of cerebellar lobules and voxels, and performed traditional univariate analyses in addition to running the machine learning prediction models. We finally evaluated the specificity of any cerebellar effects by testing for structure-function associations across brain-wide regions-of-interest (ROIs), tested whether associations with specific symptom domains were independent of associations with general cognitive function (26,27) and general psychopathology (15), and controlled for potentially confounding variables such as MRI data quality (28), parental education level (29), use of psychoactive substances (30) and psychiatric assessment strategy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, total sedentary time was selectively related to lower gray matter in the cerebellum and, in turn, the cerebellum was positively associated with crystallized intelligence, but not with fluid intelligence. First, this may not be a direct association (i.e., more total sedentary time), but an indirect influence (lower physical activity levels) affecting the key role that the cerebellum has in motor control and movement [43][44][45]. Second, the importance of the cerebellum for intelligence has been previously reported in some populations, and the specific association with crystallized, rather than fluid, intelligence may be supported by previous functional imaging studies showing cerebellar activation in relation to language, attention and mental imagery [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, independent components analysis was used to identify brain networks based on similar gray matter patterns across 92 healthy individuals aged 17 to 48 years. The cerebello-parietal network identified in this analysis was associated with an estimate of IQ, where greater loading of this network (i.e., greater inferior parietal lobe and cerebellar Crus II gray matter co-occurrence) predicted higher IQ (Yoon et al, 2017). Earlier work using voxel-based morphometry showed that bilateral cerebellar gray matter was associated with general cognitive ability in older adults with a mean age of 69 years (Hogan et al, 2011).…”
Section: Discussionmentioning
confidence: 63%